Rapid synthesis of graphene by chemical vapor deposition using liquefied petroleum gas as precursor - Lee, Imbok; Bae, Dong Jae; Lee, Won Ki; Yang, Cheol-Min; Cho, Sung Won; Nam, Jungtae; Lee, Dong Yun; Jang, A-Rang; Shin, Hyeon Suk; Hwang, Jun Yeon; Hong, Suklyun; Kim, Keun Soo (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
In this study, the rapid synthesis of graphene via chemical vapor deposition (CVD) using liquefied petroleum gas (LPG), a common and low-cost carbon source majorly composed of butane and propane, as the precursor is investigated. For the synthesis of high-quality graphene, the growth conditions are optimized by controlling CVD parameters such as growth time, temperature, gas amount, and flow rate. Thus, graphene is successfully obtained from LPG in a short time. This synthesis is 10 times faster than that the conventional synthesis using methane as the carbon source. In the X-ray photoelectron spectra, the rapidly grown graphene samples obtained from LPG show small S2p signals due to the presence of few tens ppm ethanethiol in commercial LPG. In addition, graphene is synthesized using a hydrogen and LPG mixture to investigate the quality of graphene. Both samples are characterized by their peak positions and full width at half maximum values of the G and 2D peaks in the Raman spectra and Dirac points in the electrical measurements. In particular, the Dirac points of the graphene sample obtained with a growth time of 1 min sample appear around -22 V-G and the sample's mobility is about 1600 cm(2)/V,s. (c) 2019 Published by Elsevier Ltd.
Keywords: DOPED GRAPHENE; TRANSPORT